Efektivitas Konseling Kelompok Menggunakan Teknik Self-Management untuk Mereduksi Prokrastinasi Akademik - Dwi Yuniar Permatasari; Maghfirotul Lathifah (Universitas Nusantara PGRI Kediri, 2025)
Academic procrastination remains a major challenge for high school students as it often decreases learning achievement and weakens academic responsibility. This study aimed to examine the effectiveness of group counseling using the self-management technique in reducing students’ academic procrastination, and the results indicated a significant decrease from the high to the moderate category after six treatment sessions. The research employed a quantitative approach with a pre-experimental one group pretest–posttest design involving five tenth-grade students with high levels of procrastination. The instrument used was a Likert-type academic procrastination scale, and data were analyzed using the Wilcoxon Signed Rank Test. The analysis revealed a significance value of 0.041 < 0.05, confirming that the hypothesis was accepted. These findings demonstrate that the self-management technique is effective in helping students regulate themselves, improve awareness, and build academic responsibility. Nevertheless, limitations related to sample size, absence of a control group, and short treatment duration suggest the need for further studies with stronger designs.